Sanksi Pidana Terhadap Pidana Penganiayaan yang Mengakibatkan Luka Berat - I Kadek Betit Pranata Suma; I Wayan Rideng; I Ketut Widia (Fakultas Hukum Universitas Warmadewa, 2021)
The problem that often occurs in the community is persecution. Based on the decision issued by the Semarapura District Court Number: 67 / Pid.B / 20016 / PN.Srp A case of persecution has occurred. The formulation of the problem in this paper, namely: (1) How are the provisions for the Criminal Act of Persecution? (2) How do judges impose sanctions in the Crime of Persecution which results in serious injuries (case study of the Semarapura District Court Number: 67 / Pid.B /2016 / PN.Srp)? This study uses a normative legal research method, using the Law Approach, Case Approach, and Conceptual Approach. Source of Primary and Secondary Legal Materials. Document and literature study. By studying descriptively. Criminal action regulation itself has been included in the KUHP (Criminal Code) in CHAPTER XX. Based on the Judge's Decision Number: 67 / Pid.B / 2016 / PN.Srp, the defendant has been sentenced to 1 (one) year in prison. Before making a decision, the Panel of Judges made considerations from both juridical and psychological and sociological aspects.